Renal iron accumulation occurs in lupus nephritis and iron chelation delays the onset of albuminuria. Issue 1 (December 2017) - Marks, Eileen; Bonnemaison, Mathilde; Brusnahan, Susan; Zhang, Wenting; Fan, Wei; Garrison, Jered; Boesen, Erika
Abstract Proteins involved in iron homeostasis have been identified as biomarkers for lupus nephritis, a serious complication of systemic lupus erythematosus (SLE). We tested the hypothesis that renal iron accumulation occurs and contributes to renal injury in SLE. Renal non-heme iron levels were increased in the (New Zealand Black x New Zealand White) F1 (NZB/W) mouse model of lupus nephritis compared with healthy New Zealand White (NZW) mice in an age- and strain-dependent manner. Biodistribution studies revealed increased transferrin-bound iron accumulation in the kidneys of albuminuric NZB/W mice, but no difference in the accumulation of non-transferrin bound iron or ferritin. Transferrin excretion was significantly increased in albuminuric NZB/W mice, indicating enhanced tubular exposure and potential for enhanced tubular uptake following filtration. Expression of transferrin receptor and 24p3R were reduced in tubules from NZB/W compared to NZW mice, while ferroportin expression was unchanged and ferritin expression increased, consistent with increased iron accumulation and compensatory downregulation of uptake pathways. Treatment of NZB/W mice with the iron chelator deferiprone significantly delayed the onset of albuminuria and reduced blood urea nitrogen concentrations. Together, these findings suggest that pathological changes in renal iron homeostasis occurs in lupus nephritis, contributing to the development of kidney injury.